Análise da expressão dos colágenos tipo I e tipo III no lábio glenoidal de fetos humanos - Felipe, Marcos Rainier de Brito (2024)
Glenohumeral dislocation is a frequent and disabling condition that primarily affects young patients, although it can also occur in the elderly people. This joint is the most mobile in the human body and, due to this characteristic, requires the proper functioning of both static and dynamic stabilizers to prevent the occurrence of such a disorder. In anterior dislocations, wich are the most common, there is often damage to the glenoid labrum, particularly in the anteroinferior portion. Posterior dislocations are rare and typically associated with high-energy trauma. The aim of this study is to analyze the expression of type I collagen – which is thicker and more resistant – and type III collagen – which is more extensible and pliable – in human fetuses that have not undergone any previous biomechanical alterations. The composition of these collagens was evaluated in human fetuses at gestacional ages ranging from 25 weeks to 31 weeks and 5 days. To assess this, Picrosirius Red staining was employed, with imagens being analyzed based on the percentage of collagen area exhibiting yellow-red birefringence – indicative of type I collagen – and a greenish-white area – associated with type III collagen. Type I collagen was found to be more prevalent across all samples, although a higher proportion of type III collagen was observed in fetuses compared to adult patients. The posterior labrum was shown to be richer in type I collagen when compared to the anterior labrum. These findings are consistent with the pathophysiology of the condition, which indicates shoulder instability secondary to labral injury in young patients and to rotator cuff injury in older individuals, as well as with epidemiological data showing greater incidence of anterior dislocations relative to posterior ones.